Prospective evaluation of the OKN K-SeT assay, a new multiplex immunochromatographic test for the rapid detection of OXA-48-like, KPC and NDM carbapenemases. (22nd March 2017) - Glupczynski, Youri; Jousset, Agnès; Evrard, Stéphanie; Bonnin, Rémy A.; Huang, Te-Din; Dortet, Laurent; Bogaerts, Pierre; Naas, Thierry
Abstract: Objectives: There is an urgent need for accurate and fast diagnostic tests capable of identifying carbapenemase producers. Here, we assessed the performance of a new multiplex lateral flow assay (OKN K -SeT) for the rapid detection of OXA-48-like, KPC and NDM carbapenemase-producing Enterobacteriaceae from culture colonies. Methods: Two hundred collection isolates with characterized β-lactamase content and 183 non-duplicate consecutive isolates referred to two National Reference Centres over a 2 month period in 2016 were used to evaluate the OKN K -SeT assay. Results: The assay correctly detected all 42 OXA-48-like-, 27 KPC- and 30 NDM-producing isolates from the collection panel, including 7 isolates that co-produced NDM and OXA-181 carbapenemases. No cross-reactivity was observed with non-targeted carbapenemases ( n  =   41) or with non-carbapenemase producers ( n  =   60). Prospectively, all OXA-48-like ( n  =   69), KPC ( n  =   9) and NDM ( n  =   19) carbapenemase-producing Enterobacteriaceae isolates were correctly detected, while 11 carbapenemase producers not targeted by the assay went undetected [VIM ( n  =   8) and OXA-23/OXA-58-like ( n  =   3)]. Overall, the sensitivity and specificity of the assay were 100%. Conclusions: The OKN assay is efficient, rapid and easy to implement in the workflow of a clinical microbiology laboratory for the confirmation of OXA-48, NDM and KPC carbapenemases. This test represents a powerful diagnostic tool as it enables the rapid detection of the most clinically important carbapenemases without the need for more costly and less frequently available molecular assays.